Direct Investment In The U.S. Balance Of Payments–A Portfolio Approach - Martin F.J. Prachowny (Queen's University, Department of Economics, 1969)
The active control and operation of firms in other countries implied by direct foreign investment has dominated the international investment position of the U.S. vis-a-vis the rest of the world. At the end of 1967, 73% of U.S.long term foreign assets were held in the form of direct investment. On the other side of the coin, 35% of foreign long-term assets held in the U.S. were in this category. It is the purpose of this paper to explain the demand for these direct investment assets, both U.S. investment abroad and foreign investment in the U.S.
Keywords: 330